Directive Speech Acts of Asian Characters in the Movie Shang-Chi and the Legend of the Ten Rings: Pragmatic Structures and Directive Strategies - Jarudecharat, Jeerapan; Worathumrong, Sakulrat (LEARN Journal: Language Education and Acquisition Research Network, 2023)
Superhero films have become a popular cinematic genre that has attracted the attention of scholars, many of whom focus on the films’ dialogues. Through a pragmatic approach, this small-scale study investigates how directive speech acts are represented by the three Asian characters in the superhero movie Shang-Chi and the Legend of the Ten Rings. Based on previous research, the directive speech acts in the film were extracted and analyzed, and a directive classification taxonomy was created to categorize pragmatic structures and strategies of directive speech acts. Of 342 directive utterances, the characters tend to favor both [H] and (S) oriented structures with more preference toward Single[H] and (S)+[H] structures. Of the 5 directive strategies, Nonsentential, Direct, and Non-Conventionally Indirect/Hint are the preferred strategies over the Conventionally Direct and Hybrid ones. Such preference could be mapped along the directness continuum from the most direct force strategy, Direct directive strategy, to the least direct force strategy, Non-Conventionally Indirect/Hint. The findings may contribute to further exploration of pragmatic features, especially the linguistic constructions of the Nonsentential directive strategy and its function in films, and movie script writing.